FACTORS AFFECTING CEREAL GROWTH IN A FARM RATNIEKI - Sprinģe, Zaiga; Teirumnieka, Ērika (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
Crop production is the most important crop production, since grain production contributes to the economic and political stability of any country, and the well-being of its citizens. The scientific paper summarizes information on the soil's chemical properties. Performed soil samples of the farm "Ratinieki" in the amount of soil, pH and electrical conductivity analysis of soil. On the basis of the research carried out, conclusions were made on the conditions of cereal cultivation on the holding.